2015
DOI: 10.1038/mp.2015.175
|View full text |Cite
|
Sign up to set email alerts
|

Dnmt3a2: a hub for enhancing cognitive functions

Abstract: The mechanisms responsible for fear memory formation and extinction are far from being understood. Uncovering the molecules and mechanisms regulating these processes is vital for identifying molecular targets for the development of novel therapeutic strategies for anxiety and fear disorders. Cognitive abilities require the activation of gene expression necessary to the consolidation of lasting changes in neuronal function. In this study we established a key role for an epigenetic factor, the de novo DNA methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 41 publications
3
53
0
Order By: Relevance
“…Next, we determined the effect of Dnmt3a2 overexpression within DG ensembles on cognitive function. Before performing the memory test, we habituated the mice to the experimental room and experimenter at a time point for which viral expression was confirmed to be almost undetectable 14,20 (Fig. 1c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we determined the effect of Dnmt3a2 overexpression within DG ensembles on cognitive function. Before performing the memory test, we habituated the mice to the experimental room and experimenter at a time point for which viral expression was confirmed to be almost undetectable 14,20 (Fig. 1c).…”
Section: Resultsmentioning
confidence: 99%
“…Recently developed technologies 10,11 allowed us to manipulate the levels of a DNA methyltransferase (Dnmt) specifically within hippocampal neuronal ensembles formed after contextual fear learning and to investigate the consequences of this manipulation for the strength of fear memory and stability of the engram. In particular, we elevated the levels of the de novo DNA methyltransferase (Dnmt3a2) in the dentate gyrus (DG) of the mouse hippocampus, as Dnmt3a2 expression is regulated by neuronal activity 12 and has established functions in long-lasting neuronal adaptations [13][14][15] . We showed that reinforcing DNA methylation-related mechanisms through Dnmt3a2 overexpression within memory-encoding neuronal ensembles specifically during consolidation was sufficient to strengthen contextual fear memory and the stability of the engram.…”
mentioning
confidence: 99%
“…The DNMT3a gene codes for two isoforms, DNMT3a1 and DNMT3a2 . Recent studies showed that expression of DNMT3a2 but not that of DNMT3a1 is regulated by neuronal activity in the hippocampus and that DNMT3a2 is required for the formation and extinction of fear memory . On the other side, DNMT3a2 but not DNMT3a1 in the NAc shell is required for cue‐induced reinstatement and incubation of cocaine seeking .…”
Section: Discussionmentioning
confidence: 99%
“…TET3 occupancy was found at the gephyrin promoter and gephyrin mRNA levels were increased after fear extinction learning. Therefore, TET enzymes seem to affect fear extinction by changing the pattern of 5-hmC and hence the expression of genes important for extinction, which were further shown to be positively correlated with the expression of the DNA methyltransferase DNMT3a2 (Oliveira et al, 2016). Viral-mediated manipulation of DNMT3a2 levels in the hippocampus revealed that overexpression of DNMT3a2 leads to an increase in c-fos and Arc mRNA levels during extinction memory consolidation.…”
Section: Dna Methylation In Fear Memory Reconsolidation and Extinctionmentioning
confidence: 96%
“…During the last decade, epigenetic mechanisms have been the focus of studies examining long-term adaptations such as memory formation as they have the potential to make persistent changes at the cellular level that may ultimately lead to long-term behavioral changes (Sweatt, 2009; Fischer, 2014; Jarome and Lubin, 2014; Oliveira, 2016). The main epigenetic mechanisms that directly affect chromatin structure examined in the learning and memory field to date are histone modification (Barrett and Wood, 2008), DNA modification (Baker-Andresen et al, 2013b; Alaghband et al, 2015; Oliveira, 2016) and nucleosome remodeling (Vogel-Ciernia and Wood, 2014; López and Wood, 2015).…”
Section: Overview Of Epigenetic Mechanisms Studied In Fear Processesmentioning
confidence: 99%